Networks, incentives and technology adoption: evidence from a randomised experiment in Uganda - Kelvin, Mashisia Shikuku; Mequanint B, Melesse (Oxford Publishing Limited (England), 2020)
We use data from a randomised experiment in Uganda to examine effects of incentives on the decision to adopt drought-tolerant maize varieties (DTMVs) and mechanisms through which effects occur. We find that social recognition (SR) incentives to a random subset of trained farmers – disseminating farmers (DFs) – increase knowledge transmission from DFs to their co-villagers and change information networks of both DFs and their neighbours. SR also increases DFs’ likelihood of adopting DTMVs. However, the corresponding results for private material rewards are not conclusively strong. We find no evidence that incentives for knowledge diffusion increase the likelihood of co-villagers adopting DTMVs.
Keywords: Adoption of innovations, Drought, Drought resistance, Farmers, Incentives, Maize, Natural disasters, Rewards, Social interactions ,Technology, Technology adoption, Technology utilization